Oil-soluble zinc oxide dispersion liquid as well as preparation method and application thereof

The oil-soluble zinc oxide dispersion method addresses the limitations of conventional zinc oxide nanomaterials by forming stable, uniform electronic transport layers for calcium titanate solar cells, improving their efficiency and stability and enabling high-precision manufacturing applications.

CN119677298AActive Publication Date: 2025-03-21XIAN POLYMER LIGHT TECH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411839017.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Conventional zinc oxide nanomaterials in reverse structure devices are limited due to their solubility in ethanol, which dissolves calcium titanate crystals, and their alkaline nature, which further damages the calcium titanate structure, necessitating a solvent that effectively disperses zinc oxide without causing structural breakdown.

Method used

A method for preparing an oil-soluble zinc oxide dispersion by forming a transparent reaction mixture with a zinc salt and metal dopant in a first organic solvent, adding a base and particle size regulator in a second solvent, followed by addition of ethyl acetate and organic ligands to achieve stable, oil-soluble zinc oxide nanoparticles.

Benefits of technology

The method results in a stable, uniform electronic transport layer for calcium titanate solar cells, enhancing their photovoltaic efficiency and long-term stability, with potential applications in high-precision manufacturing techniques like inkjet printing and spin coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677298A_ABST
    Figure CN119677298A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solar cells, and relates to an oil-soluble zinc oxide dispersion liquid as well as a preparation method and application thereof, during preparation, thiol and organic phosphine compounds are bonded with Zn element to form a stable ligand, the ligand can be dispersed in an oily dispersion medium, free thiol on zinc oxide nano-particles can be dispersed in an oily dispersion medium, and the zinc oxide nano-particles can be dispersed in an oily dispersion medium. And the organic phosphine compound is coordinated with Pb on the perovskite, so that the purpose of passivating the perovskite is achieved, the performance of the perovskite solar cell is improved, and the service life of the perovskite solar cell is prolonged. The prepared zinc oxide dispersion liquid can be stably stored for more than one year under the condition of room temperature, great convenience is provided for wide application of the zinc oxide dispersion liquid in industrial production due to the characteristic, and the application potential of the zinc oxide dispersion liquid in high-precision and high-efficiency manufacturing processes such as ink-jet printing, ultrasonic spraying and slit coating is expanded; and new vitality is injected for the development of the field of new energy materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells and relates to an oil-soluble zinc oxide dispersion liquid and a preparation method and application thereof. Background Art

[0002] In an inverted perovskite solar cell, the hole transport layer is placed on the transparent electrode, followed by the light absorbing layer. The main advantage of this structure is that light first passes through the hole transport layer, which can make the cell have a smaller hysteresis and a higher filling rate, and the deposition of the electron transport layer does not affect the perovskite layer.

[0003] Zinc oxide, as a commonly used electron transport layer material in perovskite solar cells, has the advantages of being cheap, stable, and easy to prepare. However, conventional zinc oxide nanomaterials are dispersed in ethanol solutions, which will dissociate perovskite crystals; and the ZnO dispersion is alkaline, and alkaline substances will also destroy perovskite crystals, which limits its use in trans devices. Therefore, in order to prepare a zinc oxide dispersion that will not destroy the perovskite layer, it is necessary to select a solvent that can effectively disperse zinc oxide and will not cause perovskite dissociation. The selected solvent should avoid strong polarity to prevent the destruction of the perovskite structure, while ensuring that zinc oxide is evenly distributed in the dispersion. Experiments have found that methanol and ethanol will dissociate perovskites due to their high polarity, while low-polarity oily solvents have less damage to perovskites. Therefore, it is particularly important to study oil-soluble zinc oxide dispersions. Summary of the invention

[0004] The purpose of the present invention is to provide an oil-soluble zinc oxide dispersion and a preparation method and application thereof, so as to solve the problem that conventional zinc oxide nanomaterials in the prior art are limited in application in trans devices.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing an oil-soluble zinc oxide dispersion comprises the following steps:

[0007] S1. dissolving a zinc salt and a metal dopant in a first organic solvent to form a transparent first reaction system;

[0008] S2. Under a 10-30°C environment, dissolving the alkali and the particle size regulator in a second organic solvent to obtain an alkali solution of a specified concentration to obtain a second reaction system;

[0009] S3. At a temperature of 20-60°C, the second reaction system is uniformly added dropwise to the first reaction system, and the reaction is continued for 0.2-24 hours to obtain a mother solution of zinc oxide nanoparticles;

[0010] S4. Add ethyl acetate to the above system to precipitate and obtain zinc oxide nanomaterials;

[0011] S5. The zinc oxide nanomaterial obtained in S4 is dissolved in a second organic solution, and a ligand exchange agent of a thiol compound or an organic phosphine compound having a carbon chain number of 2 to 12 is added thereto, the reaction is carried out for 0.1 to 24 hours, and a third organic solvent is added for precipitation to precipitate zinc oxide nanoparticles after ligand exchange;

[0012] S6. Dispersing the ligand-exchanged zinc oxide nanoparticles in a fourth organic solvent to obtain an oil-soluble zinc oxide dispersion.

[0013] Furthermore, the metal dopant described in S1 is one or more of lithium salt, magnesium salt, aluminum salt, tin salt, silver salt, and zirconium salt; the first organic solvent is one of DMF dimethylformamide, DMAc dimethylacetamide, DMSO dimethyl sulfoxide, NMPN-methylpyrrolidone, THF tetrahydrofuran, and ethylene glycol monomethyl ether.

[0014] Furthermore, the particle size regulator described in S2 is a straight-chain alcohol amine with a carbon chain number of 2-4 or one of PEG200, PEG400, and PEG600, and the second organic solvent is one of methanol, ethanol, or ethylene glycol monomethyl ether.

[0015] Furthermore, the ratio of the zinc salt to the alkali is 1:(1.0-1.8) based on the amount of substance.

[0016] Furthermore, the third organic solvent described in S5 is one of acetonitrile and acetone.

[0017] The oil-soluble zinc oxide dispersion prepared by the preparation method according to any one of claims 1 to 5 comprises an inorganic zinc oxide, an organic ligand on the surface of the inorganic zinc oxide, and an oily dispersion.

[0018] Furthermore, the zinc oxide nanoparticle size is 3-5 nm and the band gap is 3.2-3.4 eV.

[0019] Furthermore, the organic ligand is one or more of thiol compounds with a carbon chain number of 2-12, one or more of alkyl phosphine and organic phosphonic acid in organic phosphorus compounds, and the total content of the ligand accounts for 5%-30% of the total weight of the entire nanomaterial.

[0020] Furthermore, the dispersion liquid is one or more of dichloromethane, chloroform, carbon tetrachloride, benzene, toluene, xylene, chlorobenzene, n-pentane, n-hexane, n-heptane, n-octane, isooctane, white oil, and liquid paraffin.

[0021] The oil-soluble zinc oxide dispersion mentioned above is used as an electron transport layer material for perovskite solar cells.

[0022] The beneficial effects of the present invention are as follows:

[0023] The zinc oxide dispersion prepared by the present invention can successfully construct a uniform electron transport layer on the perovskite film, avoiding the interference of alcohols such as methanol and ethanol on the perovskite structure, thereby greatly improving the photoelectric conversion efficiency and long-term stability of the perovskite solar cell. Secondly, the dispersion can be stably stored for more than one year at room temperature, and this feature provides great convenience for its wide application in industrial production. Finally, thanks to the excellent dispersibility of zinc oxide nanomaterials in the medium, the present invention also expands its application potential in high-precision and high-efficiency manufacturing processes such as inkjet printing, ultrasonic spraying and slit coating.

[0024] The particle size of the zinc oxide nanomaterial prepared by the present invention is controlled at 3-5nm, and it acts as an electron transport layer material on the perovskite solar cell to meet the requirements of good flatness of the prepared film, fewer film surface defects, and reduced charge accumulation at the tip of the film surface; thiol and organic phosphorus compounds can be bonded with the Zn element to form a stable ligand, and the ligand can be dispersed in an oily dispersion medium; the free thiol compounds and organic phosphorus compounds on the ZnO nanoparticles can coordinate with lead (Pb) on the perovskite, thereby achieving the purpose of passivating the perovskite and improving the performance and life of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of zinc oxide nanoparticles.

[0026] Figure 2 It is a schematic diagram of the coordination of perovskite and the surface thiol and organic phosphorus of the zinc oxide nanoparticles of the present invention.

[0027] Figure 3 This is a TEM image of zinc oxide nanoparticles prepared in the present invention.

[0028] Figure 4 This is the XRD diagram of zinc oxide nanoparticles prepared in the present invention.

[0029] Figure 5 This is the UV-visible absorption diagram of the zinc oxide nanoparticles prepared in the present invention.

[0030] Figure 6 This is the thermogravimetric analysis diagram of zinc oxide nanoparticles prepared in the present invention. DETAILED DESCRIPTION

[0031] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0032] A method for preparing an oil-soluble zinc oxide dispersion comprises the following steps:

[0033] S1. dissolving a zinc salt and a metal dopant in a first organic solvent to form a transparent first reaction system;

[0034] S2. Under a 10-30°C environment, dissolving the alkali and the particle size regulator in a second organic solvent to obtain an alkali solution of a specified concentration to obtain a second reaction system;

[0035] S3. At a temperature of 20-60°C, the second reaction system is uniformly added dropwise to the first reaction system, and the reaction is continued for 0.2-24 hours to obtain a mother solution of zinc oxide nanoparticles;

[0036] S4. Add ethyl acetate to the above system to precipitate and obtain zinc oxide nanomaterials;

[0037] S5. The zinc oxide nanomaterial obtained in S4 is dissolved in a second organic solution, and a thiol-containing linear alkane or an organic phosphorus ligand exchange agent is added thereto, the reaction is carried out for 0.1-24 hours, and a third organic solvent is added for precipitation to precipitate zinc oxide nanoparticles after ligand exchange;

[0038] S6. Dispersing the ligand-exchanged zinc oxide nanoparticles in a fourth organic solvent to obtain an oil-soluble zinc oxide dispersion.

[0039] The zinc salt described in S1 can be selected from but not limited to zinc nitrate and its hydrate, zinc stearate, zinc acetate and its hydrate, zinc isopropoxide, zinc fluoride, zinc chloride, zinc bromide, zinc oxalate and its hydrate, zinc sulfate and its hydrate, zinc phosphate and its hydrate, zinc acetylacetonate, and zinc oxide.

[0040] The base described in S2 can be selected from but not limited to KOH, NaOH, LiOH, tetramethylammonium hydroxide, tetraethylammonium hydroxide, and ammonia water;

[0041] The particle size regulator described in S2 can be selected from but not limited to linear alcohol amines with a carbon chain number of 2-4, such as ethanolamine, n-propanolamine, n-butanolamine; and PEG200, PEG400, PEG600, PEG800, PEG1000.

[0042] The ligand exchange agent described in S5 is a straight-chain alkane containing a thiol group, which can be selected from but not limited to one of n-hexyl mercaptan, n-heptyl mercaptan, n-octyl mercaptan, n-nonyl mercaptan, n-decyl mercaptan, n-undecaptan, dodecanethiol, n-tetradecanethiol, n-hexadecyl mercaptan, and n-octadecanethiol, preferably: n-hexyl mercaptan, n-octyl mercaptan, and n-dodecyl mercaptan;

[0043] The ligand exchange agent described in S5 can also be alkyl phosphines and organic phosphonic acids among organic phosphorus compounds; alkyl phosphines such as trioctyl phosphine, triphenyl phosphine, tributyl phosphine; organic phosphoric acids such as aminomethyl phosphonic acid, phenylethyl phosphonic acid, ethyl phosphoric acid, hexyl phosphonic acid, octyl phosphoric acid, etc.

[0044] The ZnO nanomaterials in the present application are not limited thereto. Different metal dopants can be selected in S1 to obtain corresponding metal-doped zinc oxide nanomaterials, as follows:

[0045] Al-doped ZnO: such as Al:ZnO (wherein the molar doping amount of Al is 1%-5%; preferably 1%, 2%, 5%);

[0046] Mg-doped ZnO: such as Mg:ZnO (wherein the molar doping amount of Mg is 1-20%; preferably 1%, 5%, 10%, 15%, 20%);

[0047] Li-doped ZnO: such as Li:ZnO (wherein the molar doping amount of Li is 1%-6%; preferably 1%, 2%, 4%, 6%);

[0048] Ag-doped ZnO: such as Ag:ZnO (wherein the molar doping amount of Ag is 1%-4%; preferably 1%, 2%, 4%);

[0049] Zr-doped ZnO: such as Zr:ZnO (wherein the molar doping amount of Zr is 1%-3%; preferably 1%, 2%, 3%);

[0050] The present invention also provides an oily zinc oxide dispersion, which is prepared according to the above method. The zinc oxide dispersion comprises zinc oxide inorganic matter, organic ligands on the surface of zinc oxide and an oily dispersion. The band gap range is calculated to be 3.2 eV-3.4 eV. The calculation method is well known to those skilled in the art, for example, it can be calculated by the Tauc Plot method, which will not be described here.

[0051] According to another aspect of the present invention, an inverted perovskite solar cell is provided, comprising an anode, a hole transport layer, a light absorption layer, an electron transport layer, and a cathode, wherein the electron transport layer is prepared from the above-mentioned zinc oxide nano-dispersion by spin coating, printing, spraying, or scraping.

[0052] Embodiment 1

[0053] S1. Dissolve 1 mmol of zinc acetate dihydrate in 100 ml of DMSO and stir to form a transparent first reaction system;

[0054] S2. At room temperature, 1.5 mmol of tetramethylammonium hydroxide pentahydrate and 2 mmol of ethanolamine were dissolved in 200 ml of ethanol to obtain a second reaction system;

[0055] S3. At 50°C, the second reaction system was added dropwise to the first reaction system at 200 ml / h, and the reaction was continued for 4 hours to obtain a mother solution of zinc oxide nanoparticles;

[0056] S4. Add ethyl acetate to the above system to precipitate and obtain zinc oxide nanomaterials;

[0057] S5. The zinc oxide nanomaterial obtained in S4 was dissolved in 50 ml of ethanol, and 1 mmol of n-octyl mercaptan and 0.5 mmol of aminomethylphosphonic acid were added thereto, and the reaction was continued for 0.5 h, and 200 ml of ethanol was added, and then 100 ml of acetonitrile was added, and the ligand-exchanged zinc oxide nanoparticles were obtained by centrifugation;

[0058] S6. The zinc oxide nanoparticles after ligand exchange can be dispersed in n-hexane to prepare a 25 mg / ml n-hexane spin coating solution, that is, the ZnO oily dispersion described in the present application is obtained;

[0059] Embodiment 2

[0060] S1. Dissolve 1 mmol of zinc isopropoxide in 100 ml of DMF and stir to form a transparent first reaction system;

[0061] S2. At room temperature, 1.5 mmol KOH and 1 mmol n-propanolamine were dissolved in 200 ml of ethylene glycol monomethyl ether to obtain a second reaction system;

[0062] S3. At 30°C, the second reaction system was added dropwise to the first reaction system at 200 ml / h, and the reaction was continued for 6 hours to obtain a mother solution of zinc oxide nanoparticles;

[0063] S4. Add ethyl acetate to the above system to precipitate and obtain zinc oxide nanomaterials;

[0064] S5. The zinc oxide nanomaterial obtained in S4 was dissolved in 50 ml of ethylene glycol monomethyl ether, and 1 mmol of n-dodecyl mercaptan and 0.2 mmol of trioctyl phosphine were added thereto. The reaction was continued for 1 h, and 200 ml of ethylene glycol monomethyl ether was added, and then 100 ml of acetone was added, and the ligand-exchanged zinc oxide nanoparticles were obtained by centrifugation.

[0065] S6. The ligand-exchanged zinc oxide nanoparticles can be dispersed in n-octane to prepare a 25 mg / ml n-octane spin coating solution to obtain the ZnO oily dispersion described in the present application;

[0066] Embodiment 3

[0067] S1. Dissolve 1mmol zinc acetate dihydrate and 0.2mmol aluminum isopropoxide in 100ml DMSO and stir to form a transparent first reaction system;

[0068] S2. Under room temperature, 1.5 mmol tetramethylammonium hydroxide pentahydrate and 0.2 mmol PEG400 were dissolved in 200 ml ethanol to obtain a second reaction system;

[0069] S3. At 40°C, the second reaction system was added dropwise to the first reaction system at 200 ml / h, and the reaction was continued for 2 hours to obtain a mother solution of aluminum-doped zinc oxide nanoparticles;

[0070] S4. adding ethyl acetate to the above system to precipitate and obtain aluminum-doped zinc oxide nanomaterial;

[0071] S5. The aluminum-doped zinc oxide nanomaterial obtained in S4 was dissolved in 50 ml of ethanol, and 1 mmol of ethyl mercaptan and ethylphosphonic acid were added thereto, and the reaction was continued for 0.5 h, and 200 ml of ethanol was added, and then 100 ml of acetonitrile was added, and the aluminum-doped zinc oxide nanoparticles after ligand exchange were obtained by centrifugation;

[0072] S6. The aluminum-doped zinc oxide nanoparticles after ligand exchange can be dispersed in n-octane to prepare a 25 mg / ml n-octane spin coating solution, that is, the oily aluminum-doped zinc oxide dispersion described in the present application is obtained;

[0073] Embodiment 4

[0074] S1. 1 mmol of Mg:ZnO (5 mol% Mg) nanomaterial was ultrasonically dispersed in 50 ml of ethylene glycol methyl ether, and 1 mmol of n-octyl mercaptan and 0.6 mmol of octyl phosphoric acid were added thereto, and the reaction was stirred for 2 h, and 100 ml of ethylene glycol methyl ether was added, and then 100 ml of acetone was added, and the magnesium-doped zinc oxide nanoparticles after ligand exchange were obtained by centrifugation;

[0075] S2. The zinc oxide nanoparticles after ligand exchange can be dispersed in chlorobenzene to prepare a 25 mg / ml chlorobenzene spin coating solution to obtain the Mg:ZnO chlorobenzene dispersion described in the present application;

[0076] Embodiment 5

[0077] The present embodiment provides an inverted solar perovskite cell device, and its manufacturing method includes the following steps: spin coating a layer of NiOx nanomaterial on the IT0 anode layer, and then annealing at 150°C for 30 minutes to form a hole transport layer; spin coating a perovskite solution on the hole transport layer as a carrier to form an absorption layer; spin coating an organic dispersion of ZnO in the embodiment on the absorption layer, annealing at 80°C, and forming an electron transport layer after drying; finally, evaporating an Au cathode electrode layer, and encapsulating to form a perovskite solar cell device, and the device performance structure is described in Table 1.

[0078] Comparative Example 1

[0079] S1. Dissolve 1 mmol of zinc acetate dihydrate in 100 ml of ethanol and stir to form a first reaction system;

[0080] S2. Under room temperature, 1.5 mmol KOH was dissolved in 200 ml ethanol to obtain a second reaction system;

[0081] S3. At 50°C, the second reaction system was added dropwise to the first reaction system at 200 ml / h, and the reaction was continued for 4 hours to obtain a mother solution of zinc oxide nanoparticles;

[0082] S4. Add ethyl acetate to the above system to precipitate and obtain zinc oxide nanomaterials;

[0083] S5. Add ethanol solution to the zinc oxide nanomaterial to prepare 25 mg / ml ethanol spin coating solution to obtain the ZnO ethanol dispersion described in the present application;

[0084]

[0085]

[0086] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing an oil-soluble zinc oxide dispersion, characterized in that: The following steps are involved: S1. dissolving a zinc salt and a metal dopant in a first organic solvent to form a transparent first reaction system; S2. Under a 10-30°C environment, dissolving the alkali and the particle size regulator in a second organic solvent to obtain an alkali solution of a specified concentration to obtain a second reaction system; S3. At a temperature of 20-60°C, the second reaction system is uniformly added dropwise to the first reaction system, and the reaction is continued for 0.2-24 hours to obtain a mother solution of zinc oxide nanoparticles; S4. Add ethyl acetate to the above system to precipitate and obtain zinc oxide nanomaterials; S5. The zinc oxide nanomaterial obtained in S4 is dissolved in a second organic solution, and a ligand exchange agent of a thiol compound or an organic phosphine compound having a carbon chain number of 2 to 12 is added thereto, the reaction is carried out for 0.1 to 24 hours, and a third organic solvent is added for precipitation to precipitate zinc oxide nanoparticles after ligand exchange; S6. Dispersing the ligand-exchanged zinc oxide nanoparticles in a fourth organic solvent to obtain an oil-soluble zinc oxide dispersion.

2. The method for preparing an oil-soluble zinc oxide dispersion according to claim 1, wherein: The metal dopant described in S1 is one or more of lithium salt, magnesium salt, aluminum salt, tin salt, silver salt, and zirconium salt; the first organic solvent is one of DMF dimethylformamide, DMAc dimethylacetamide, DMSO dimethyl sulfoxide, NMPN-methylpyrrolidone, THF tetrahydrofuran, and ethylene glycol monomethyl ether.

3. The method for preparing an oil-soluble zinc oxide dispersion according to claim 1, wherein: The particle size regulator described in S2 is a straight-chain alcohol amine with a carbon chain number of 2-4 or one of PEG200, PEG400, and PEG600, and the second organic solvent is one of methanol, ethanol, or ethylene glycol monomethyl ether.

4. The method for preparing an oil-soluble zinc oxide dispersion according to claim 1, wherein: In terms of mass, the ratio of the zinc salt to the alkali is 1:(1.0-1.8).

5. The method for preparing the oil-soluble zinc oxide dispersion according to claim 1, characterized in that: The third organic solvent described in S5 is one of acetonitrile and acetone.

6. The oil-soluble zinc oxide dispersion prepared by the preparation method according to any one of claims 1 to 5, comprising inorganic zinc oxide, organic ligands on the surface of the inorganic zinc oxide and an oily dispersion.

7. The oil-soluble zinc oxide dispersion according to claim 6, characterized in that: The ZnO nanoparticle size is 3-5nm and the band gap is 3.2-3.4eV.

8. The oil-soluble zinc oxide dispersion according to claim 6, characterized in that: The organic ligands are one or more of thiol compounds with 2-12 carbon chains, one or more of alkyl phosphine and organic phosphonic acid in organic phosphorus compounds, and the total content of the ligands accounts for 5%-30% of the total weight of the entire nano material.

9. The oil-soluble zinc oxide dispersion according to claim 6, characterized in that: The dispersion liquid is one or more of dichloromethane, chloroform, carbon tetrachloride, benzene, toluene, xylene, chlorobenzene, n-pentane, n-hexane, n-heptane, n-octane, isooctane, white oil, and liquid paraffin.

10. Use of the oil-soluble zinc oxide dispersion as claimed in claim 6 as an electron transport layer material for perovskite solar cells.

Citation Information

Patent Citations

  • Quantum dot light-emitting diode and preparation method thereof

    CN111384278A

  • Perovskite / zinc oxide heterostructure luminescent material and preparation method thereof

    CN113105885A

  • Zinc oxide nano material, preparation method thereof and luminescent device

    CN113903865A

  • Nano metal oxide and preparation method thereof, electroluminescent device and display device

    CN116156982A

  • Composite hole transport layer, inverted perovskite solar cell and preparation method of inverted perovskite solar cell

    CN118488771A